Control of lettuce bottom rot by isolates of Trichoderma spp - Pinto, Zayame Vegette [UNESP]; Cipriano, Matheus Aparecido Pereira; Santos, Amaury Da Silva Dos; Pfenning, Ludwig Heinrich; Patrício, Flávia Rodrigues Alves (Grupo Paulista de Fitopatologia, 2014)
Bottom rot, caused by Rhizoctonia solani AG 1-IB, is an important disease affecting lettuce in Brazil, where its biological control with Trichoderma was not developed yet. The present study was carried out with the aim of selecting Trichoderma isolates to be used in the control of lettuce bottom rot. Forty-six Trichoderma isolates, obtained with baits containing mycelia of the pathogen, were evaluated in experiments carried out in vitro and in vivo in a greenhouse in two steps. In the laboratory, the isolates were evaluated for their capabilities of parasitizing and producing toxic metabolic substances that could inhibit the pathogen mycelial growth. In the first step of the in vivo experiments, the number and the dry weight of lettuce seedlings of the cultivar White Boston were evaluated. In the second step, 12 isolates that were efficient in the first step and showed rapid growth and abundant sporulation in the laboratory were tested for their capability of controlling bottom rot in two repeated experiments, and had their species identified. The majority of the isolates of Trichoderma spp. (76%) showed high capacity for parasitism and 50% of them produced toxic metabolites capable of inhibiting 60-100% of R. solani AG1-IB mycelial growth. Twenty-four isolates increased the number and 23 isolates increased the dry weight of lettuce seedlings inoculated with the pathogen in the first step of the in vivo experiments.In both experiments of the second step, two isolates of T. virens, IBLF 04 and IBLF 50, reduced the severity of bottom rot and increased the number and the dry weight of lettuce seedlings inoculated with R. solani AG1-IB. These isolates had shown a high capacity for parasitism and production of toxic metabolic substances, indicating that the in vitro and in vivo steps employed in the present study were efficient in selecting antagonists to be used for the control of lettuce bottom rot.

A queima da saia, causada por Rhizoctonia solani AG 1-IB, é uma importante doença da cultura da alface no Brasil, para a qual o controle biológico com Trichoderma não foi desenvolvido até o momento no país. O presente estudo foi realizado com o objetivo de selecionar isolados de Trichoderma para serem usados para o controle da queima da saia em alface. Quarenta e seis isolados de Trichoderma obtidos com iscas contendo micélio do patógeno foram avaliados em experimentos conduzidos in vitro e in vivo, os quais foram realizados em casa de vegetação, em duas fases.Em laboratório os isolados foram avaliados com relação às capacidades de parasitismo e de produção de substâncias metabólicas tóxicas, com capacidade de inibir o crescimento micelial do patógeno. Na primeira fase dos experimentos in vivo, foram avaliados o número e a massa seca de plântulas de alface da cultivar White Boston. Na segunda fase, 12 isolados eficientes na primeira fase e que também apresentaram rápido crescimento e esporulação abundante em laboratório, foram avaliados com relação à sua capacidade de controlar a queima da saia em dois experimentos repetidos, e também tiveram suas espécies identificadas. A maioria dos isolados de Trichoderma spp. (76%) apresentou elevada capacidade de parasitismo e 50% dos isolados produzim metabólitos tóxicos capazes de inibir 60-100% do crescimento micelial de R. solani AG1-1-B. Vinte e quatro isolados promoveram aumento do número e 23 na massa seca de plântulas de alface inoculadas com o patógeno na primeira fase dos experimentos in vivo. Nos dois experimentos da segunda fase dois isolados de T. virens, IBLF 04 e IBLF 50, reduziram a severidade da queima da saia e promoveram o aumento do número e da massa seca das plântulas de alface inoculadas com R. solani AG 1-IB. Esses isolados haviam apresentado elevada capacidade de parasitismo e de produção de substâncias metabólicas tóxicas, indicando que as fases in vitro e in vivo empregadas no presente estudo foram eficientes para a seleção dos antagonistas a serem utilizados para o controle da queima da saia em alface.
Controle da queima da saia em alface com isolados de Trichoderma spp
Keywords: controle biológico; Rhizoctonia solani; Lactuca sativa; biological control; Rhizoctonia solani; Lactuca sativa